Auxiliary Cadences and the Binary Rondo - Joel Galand (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
James Hepokoski’s and Warren Darcy’s Elements of Sonata Theory is fast emerging as one the most influential theories of form to have been advanced in recent decades. The authors only briefly discuss some of the Schenkerian implications of their work, but what they have to say is intriguing and opens up broad avenues of future research. This essay contributes to that research program. It focuses on the Schenkerian notion of the auxiliary cadence and how it manifests itself in a formal design that up until recently has not been well understood, namely the category of rondo that Hepokoski and Darcy have termed the Type 41 sonata. To that end, I analyze the role that the auxiliary cadence plays in a group of four closely-related Type 41 rondos: the finales of Beethoven’s Piano Concerto, Op. 58; his String Quartet Op. 59/2; Brahms’s Piano Concerto, Op. 83; and his String Quintet, Op. 111. I also touch briefly on the finale to Schubert’s late Piano Sonata in B-flat, D. 960. It is possible—although it cannot be proven—that the Beethoven finales provided a model for Schubert’s and Brahms’s. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).